PENGARUH ORGANISASI KEMAHASISWAAN TERHADAP PENGEMBANGAN CIVIC PARTICIPATORY SKILLS MAHASISWA (STUDI KASUS HIMAPRODI PPKn FKIP UNIVERSITAS RIAU PERIODE 2019-2020) - Rianti, Dewi; Hambali, Hambali; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the lack of participation or civic participatory skills that exist in active students who are not at all members of student organizations in the Pancasila and Citizenship Education Study Program (Prodi PPKn), Faculty of Teacher Training and Education (FKIP), University of Riau. The formulation of the problem in this study is how the influence of student organizations on the development of student civic participatory skills (case study of the Student Association (Himaprodi) PPKn FKIP Riau University for the period 2019-2020). The research objective was to determine how the influence of student organizations on the development of student civic participatory skills (a case study of the Himaprodi PPKn FKIP Riau University for the period 2019-2020). In this study, the sample size was 31 respondents. Sampling in this study using proportional sampling technique. This research method is descriptive quantitative, data collection instruments used in this research, namely, a questionnaire consisting of 5 indicators with 20 statements. Based on the results of research on the influence of student organizations on the development of student civic participatory skills (case study of the PPKn FKIP Riau University Himaprodi period 2019-2020), it is concluded that: There is a significant influence between student organizations on the development of student civic participatory skills in Himaprodi PPKn FKIP University Riau for the period 2019-2020. So the hypothesis in this study is accepted, based on the coefficient of determination test, which is carried out to see how much the contribution of the independent variable to the dependent variable, it is known that the R value is positive, namely 0.663, the value of the relationship (R) is 0.663 while the coefficient of determination (R Square) is 0.440. which implies that the effect of the independent variable (Student Organization) on the dependent variable (Student civic participatory skills) is 66.3%.Key Words: Influence, Student Organization, Civic Participatory Skills